2012
DOI: 10.1007/s10544-012-9660-9
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of molecules into cells using localized single cell electroporation on ITO micro-electrode based transparent chip

Abstract: Single cell electroporation is one of the nonviral method which successfully allows transfection of exogenous macromolecules into individual living cell. We present localized cell membrane electroporation at single-cell level by using indium tin oxide (ITO) based transparent micro-electrodes chip with inverted microscope. A focused ion beam (FIB) technique has been successfully deployed to fabricate transparent ITO micro-electrodes with submicron gaps, which can generate more intense electric field to produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Recently single cell membrane nano-electroporation in a localized region has attracted much attention due to high transfection rate and high cell viability. [8][9][10][11][12] However the effect of highly intensive electric field with the variation of TMP in a local region of the single cell membrane was not well studied previously. Higher electric field effects the whole single cell (familiar as single cell electroporation (SCEP)) to cause cell lysis easily.…”
mentioning
confidence: 99%
“…Recently single cell membrane nano-electroporation in a localized region has attracted much attention due to high transfection rate and high cell viability. [8][9][10][11][12] However the effect of highly intensive electric field with the variation of TMP in a local region of the single cell membrane was not well studied previously. Higher electric field effects the whole single cell (familiar as single cell electroporation (SCEP)) to cause cell lysis easily.…”
mentioning
confidence: 99%
“…To apply a very high electric field in between two microchannels, a transfection agent was delivered through the nanochannel using an electrophoretically driven process and finally drugs were delivered inside a single cell through a very small area of the cell membrane. In 2012, Chen et al demonstrated another localized single cell membrane electroporation usimg ITO microelectrode based transparent chip [27]. Figure 14 shows microfluidic localized single cell membrane electroporation device.…”
Section: Lscmep For Cell Transfectionmentioning
confidence: 99%
“…As a result, single cell manipulation can be performed from population of cells together. These devices can analyze cell to cell behavior with their organelle, their orientation, changes of cell size and shape with different polarities of electric fields [14,23,24,26,27]. On the other hand, bulk electroporation needs two large electrodes surrounding millions of cells together and a homogeneous electric field is applied to electroporates millions of cells at once.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations